Characterization of S-layer proteins of potential probiotic starter culture Lactobacillus brevis SF9B isolated from sauerkraut. (July 2018) - Banić, Martina; Uroić, Ksenija; Leboš Pavunc, Andreja; Novak, Jasna; Zorić, Katarina; Durgo, Ksenija; Petković, Hrvoje; Jamnik, Polona; Kazazić, Saša; Kazazić, Snježana; Radović, Slobodanka; Scalabrin, Simone; et al.
Abstract: S-layers represent the simplest biological membranes developed during the evolution and are one of the most abundant biopolymers on Earth. Current fundamental and applied research aim to reveal the chemical structure, morphogenesis and function of S-layer proteins (Slps). This is the first paper that describes the Slps of certain Lactobacillus brevis strain isolated from sauerkraut. The whole genome sequence (WGS) analysis of the L. brevis SF9B strain uncovered three genes encoding the putative Slps, but merely one, identified as similar to the SlpB of L. brevis ATCC 14869, was expressed. Slp-expressing SF9B cells exhibited increased survival in simulated gastrointestinal (GI) conditions and during freeze-drying. Their survival in stress conditions was additionally enhanced by microencapsulation, especially when using alginate with gelatine as a matrix. Thus prepared cells were subjected to simulated GI conditions and their mortality was only 0.28 ± 0.45 log CFU/mL. Furthermore, a correlation between the high surface hydrophobicity and the remarkable aggregative capacity of SF9B strain was established. The results indicate a prominent role of Slps in adhesion to mucin, extracellular matrix (ECM) proteins, and particularly to Caco-2 cells, where the removal of Slps utterly abolished the adhesiveness of SF9B cells for 7.78 ± 0.25 log CFU/mL. Highlights: S-layer protein of L. brevis SF9B is 65% similar to SlpB of L. brevis ATCC 14869. S-layer protein of L. brevis SF9B has theoretical MW of 50.9 kDa and pI of 9.54 S-layer positively affects probiotic properties of L. brevis SF9B. L. brevis SF9B is a potential probiotic starter culture for sauerkraut production.